Focused high‐energy extracorporeal shockwaves as supplemental treatment in a rabbit model of fracture‐related infection. Issue 6 (25th December 2019) - Puetzler, Jan; Milstrey, Alexander; Everding, Jens; Raschke, Michael; Arens, Daniel; Zeiter, Stephan; Geoff Richards, Robert; Fintan Moriarty, Thomas
Abstract: Focused high‐energy extracorporeal shockwave therapy (fhESWT) is used to improve fracture healing in cases of nonunion. In addition, it has been shown to have direct antibacterial effects. We evaluated fhESWT as an adjunct to conventional treatment in a clinically relevant rabbit model of fracture‐related infection (FRI). A humeral osteotomy in 31 rabbits was fixed with a seven‐hole locking compression plate. FRI was established with a clinical Staphylococcus aureus isolate. After 2 weeks, a revision surgery was performed with debridement, irrigation, and implant retention. Rabbits then received: no further treatment (controls); shockwaves (4000 impulses with 23 kV at days 2 and 6 after revision); systemic antibiotics (rifampin and nafcillin); or the combination of antibiotics and shockwaves. Treatments were applied over 1 week. Blood cultures were taken before and after shockwave sessions. After another week without treatment, rabbits were euthanized and quantitative bacteriology was performed on implants and tissues to determine infection burden. Indicator organs (brain, heart, liver, lungs, kidneys, and spleen) were cultured to assess possible bacteremia. All the rabbits were infected at revision surgery as determined by the bacteriological culture of debrided materials. fhESWT in combination with antibiotic treatment lowered the bacterial burden 100‐fold compared with antibiotic treatment alone in all samples ( P = .38). This effect was most prevalent for the implant sample ( P = .08). No significant effect was seen for fhESWT alone compared with untreated controls. No signs of bacteremia occurred in blood cultures and organs. fhESWT appears safe and could be a helpful adjunct to conventional treatment in certain difficult‐to‐treat FRIs.